Effect of early and split weaning management on growth performance of Large White Yorkshire pigs - SAIKIA, KARUNA; KALITA, GIRIN; HMAR, L; GOSWAMI, R; TALUKDAR, D J; SAMANTA, A K; TOLENKHOMBA, T C (The Indian Journal of Animal Sciences, 2019)
Lactating Large White Yorkshire sows (18) with their litters were selected for the study and were divided into three groups (T1, T2, T3). In T1 and T3 groups, piglets were weaned at day 24 and 28. In group T2, heavier half of the litters were weaned at day 24 and remaining half were weaned at day 28. The piglets were reared up to 70 days of age and their performance was recorded. The result revealed that average body weight (kg) at day 70 and the ADG (g) from 1st to 10th week differed non-significantly among the groups. Nonsignificant difference was observed in pre-weaning, post-weaning and overall ADI among the different weaning groups. FCE from weaning to 10th week was similar among the different weaning groups. In conclusion, the whole litter or split litter weaning at day 24 or 28, had no effect on body weight gain, average daily gain, average daily feed intake and feed conversion efficiency of piglets. The findings may be helpful to develop managemental strategies for early weaning of piglets in Indian farm conditions.